Kausalitas Infrastruktur Jalan, Urbanisasi dan Kesejahteraan masyarakat di Indonesia - Dini Dwi Syafira; Mike Triani (Universitas Negeri Padang, 2021)
This study aims to determine: (1) Causality of road infrastructure and urbanization in Indonesia. (2) Causality of road infrastructure and public welfare in Indonesia. (3) Causality of urbanization and welfare in Indonesia. Type of Data: Secondary data in the form of time series. Sample and research: From 1987-2017. The method used in this research is the Vector Error Correlation Model Method. The results show that: (1) In the short term urbanization and community welfare do not contribute to the variability of road infrastructure in Indonesia. (2) In the long term, urbanization and community welfare each contribute to road infrastructure. (3) In the short term road infrastructure contributes to the variability of urbanization and the welfare of the community does not. (4) In the long run, people's welfare will contribute the most in influencing the variability of urbanization. (5) In the short term as well as in the long term, road infrastructure and urbanization contribute to the variability of the welfare of the people in Indonesia.